Chronically shortened rod outer segments accompany photoreceptor cell death in Choroideremia - Meschede, Ingrid P. (2020)
X-linked choroideremia (CHM) is a disease characterized by gradual retinal degeneration caused by loss of the Rab Escort Protein, REP1. Despite partial compensation by REP2 the disease is characterized by prenylation defects in multiple members of the Rab protein family that are master regulators of membrane traffic. Remarkably, the eye is the only organ affected in CHM patients, possibly because of the huge membrane traffic burden of the post mitotic photoreceptors, which synthesise outer segments, and the adjacent retinal pigment epithelium that degrades the spent portions each day. In this study, we aimed to identify defects in membrane traffic that might lead to photoreceptor cell death in CHM. In a heterozygous null female mouse model of CHM (Chmnull/WT), degeneration of the photoreceptor layer was clearly evident from increased numbers of TUNEL positive cells compared to age matched controls, small numbers of cells exhibiting signs of mitochondrial stress and greatly increased microglial infiltration. However, most rod photoreceptors exhibited remarkably normal morphology with well-formed outer segments and no discernible accumulation of transport vesicles in the inner segment. The major evidence of membrane trafficking defects was a shortening of rod outer segments that was evident at 2 months of age but remained constant over the period during which the cells die. A decrease in rhodopsin density found in the outer segment may underlie the outer segment shortening but does not lead to rhodopsin accumulation in the inner segment. Our data argue against defects in rhodopsin transport or outer segment renewal as triggers of cell death in CHM.